2001
DOI: 10.1074/jbc.m007271200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Apoptosis by Phosphatidylinositol 4,5-Bisphosphate Inhibition of Caspases, and Caspase Inactivation of Phosphatidylinositol Phosphate 5-Kinases

Abstract: Phosphoinositides such as phosphatidylinositol 3,4,5-trisphosphate and phosphatidylinositol 3,4-bisphosphate promote cell survival and protect against apoptosis by activating Akt/PKB, which phosphorylates components of the apoptotic machinery. We now report that another phosphoinositide, phosphatidylinositol 4,5-bisphosphate (PIP 2 ) is a direct inhibitor of initiator caspases 8 and 9, and their common effector caspase 3. PIP 2 inhibited procaspase 9 processing in cell extracts and in a reconstituted procaspas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 43 publications
1
47
1
Order By: Relevance
“…HIV-1 Env-mediated PIP 2 production during viral entry might therefore alter plasma membrane fluidity or viral receptor organization to favor initial HIV-1/cell interactions and promote subsequent fusion. PIP 2 has also been found to protect against cell apoptosis, alone or in a complex with gelsolin, by directly inhibiting the initiator caspases 8 and 9, as well as by binding and inhibiting their common effector, caspase 3 (37,38). Therefore it is plausible that HIV-1-triggered synthesis of PIP 2 during the first steps of the viral cycle may serve to ensure cell viability and, therefore, efficient viral infection and propagation.…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 Env-mediated PIP 2 production during viral entry might therefore alter plasma membrane fluidity or viral receptor organization to favor initial HIV-1/cell interactions and promote subsequent fusion. PIP 2 has also been found to protect against cell apoptosis, alone or in a complex with gelsolin, by directly inhibiting the initiator caspases 8 and 9, as well as by binding and inhibiting their common effector, caspase 3 (37,38). Therefore it is plausible that HIV-1-triggered synthesis of PIP 2 during the first steps of the viral cycle may serve to ensure cell viability and, therefore, efficient viral infection and propagation.…”
Section: Discussionmentioning
confidence: 99%
“…PIP5KI Overexpression-We use the isoform designation for human PIP5KIs, which is different from that for mouse (30). Hemagglutinin (HA)-tagged PIP5KI␣, -␤, -␥87, and -␥90 were cloned from cDNA provided by other laboratories.…”
Section: Methodsmentioning
confidence: 99%
“…The depletion of PtdIns(4,5)P 2 in response to stress seems to be the result of the translocation of PIP5K away from the plasma membrane, which also occurs independently of caspase activation (Halstead et al, 2006). Other studies have indicated that PIP5K can be cleaved by caspase-3 (Mejillano et al, 2001). It is therefore possible that caspase-independent inhibition of PIP5K might initially induce a reversible decrease in PtdIns(4,5)P 2 levels, whereas longer-term caspase-dependent cleavage of PIP5K maintains the depletion of cellular PtdIns(4,5)P 2 levels.…”
Section: Endo- Exo-and Phagocytosismentioning
confidence: 99%